Acts of Charity as Acts of Remembrance in the Book of Tobit - Macatangay, Francis M. (Journal for the study of the pseudepigrapha, 2013)
This article argues that charitable acts in the book of Tobit are religious acts of remembrance. On the one hand, the narrative emphasizes the practice of righteousness, the doing of what is true, and the performance of charitable deeds. On the other hand, the remembrance of God is an equally prominent motif in the story. This gives rise to the question of how remembering is linked to acts of charity. The close connection between remembering and almsgiving argues against the commonly held view that the story endorses acts of charity because such acts facilitate social cohesion and mutual support in the Diaspora. Given the theological value the narrative places on almsgiving, the book of Tobit witnesses to the emergence of a horizontal expression of service to God as part of the religious piety in Second Temple Judaism.